Evaluating Geographic Influences on Pedestrian Evacuation Using Cellular Automata: a Case Study of Sete Cidades National Park in Wildfire Scenarios - Santos, Nathália Beatriz Leonel; Lima, Danielli Araújo (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2025: Anais do XVI Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais, 2025)
The study of pedestrian evacuation dynamics is a field of much relevance for risk assessment and formation of plans aiming to minimize negative impacts in emergency situations. In this work, our objective is to create computational simulations using cellular automata around the pedestrian evacuation behavior on the Sete Cidades National Park, considering its high tourist activity. To this end, different geographical features were abstracted, with emphasis on the heterogenous vegetation and various relief altitudes, in order to evaluate the impact on evacuation times and routes. Additionally, wildfire propagation was also included in the model, introducing a realistic aspect for safety analysis on distinct regions of the park. Through this study, we sought to assist in the definition of evacuation policies on the target location, thus helping guarantee safe interactions between society and the environment1.